Functional properties of kenaf bast fibre anhydride modification enhancement with bionanocarbon in polymer nanobiocomposites - Suriani Abu Bakar (Tanjong Malim, 2021)
Functional properties of kenaf bast fibre anhydride modification enhancement with bionanocarbon in polymer nanobiocomposites by Suriani Abu Bakar